THE IMPACTS OF THE SPECIAL REGIONAL POLICY TO THE LOCAL GOVERNMENT ENFORCEMENT IN SOUTHERN THAILAND (CASE STUDY AT THE REPEL DISTRICT, KRONGPINANG, THAILAND) - Tehtae, Sareef; Eby Hara, Abubakar; Puspitaningtyas, Zarah (International Journal of Research -GRANTHAALAYAH, 2018)
Special territory policy has been using in the Southern Thailand is a central government’s policy (Bangkok) in terms of giving absolute authority to the military, to resolve the conflicts in southern Thailand. The policy includes three matters: 1) Martial law of 2547 (the regulations in state of emergency in the 2004); 2) the Emergency Decree 2548 PO-Ro-Ko (Security rules in state of emergency); 3) Internal Security Act in the 2551 PO – RO – BO (the rule in terms of internal security implementation of 2008). This paper aimed to analyzing the impacts of special regional policies on local governance in southern Thailand (case study in Repel district, Krongpinang, Thailand. This research used descriptive qualitative methodology. based on research results, can be concluded that the impacts of the implementation of special regional policy; 1) the functional disappearance of local government; 2) local government was depressed by military system; 3) society harmonization to local government (village head) decreased.